PERSEPSI MASYARAKAT TERHADAP PENGOBATAN TRADISIONAL BERDASARKAN PROFESI DI KABUPATEN PURWAKARTA - Suharti Suharti; Susi Andriani; Reti Puji Handayani (Prodi Farmasi - Universitas Al Ghifari, 2020)
Background: Necessity to get treatment through conventional pathways or traditional treatments is a fundamental attempts that need to be attempted and still continue to be carried out by studies related to treatment relationships based on the type of profession. Objectives: Seeing Purwakarta District Perception of Traditional Medicine Based on Health Profession and Non-Health Profession. Methods: This qualitative associative explanatory study is connected with a statement from the questionnaire given and searches for correlations between factors that influence the behavior of treatment searches in 137 respondents through questionnaire instruments with a Likert scale. Result: Data was obtained that Purwakarta Regency respondents represented by urban community groups, the urban community and rural communities studied from a statement of questionnaires have known the existence of traditional medicines, but non-health public perceptions related to the interests and knowledge of traditional medicine (68.8%); Potential development (69.2%); Trust in the efficacy (61.5%) and trust in the quality (standardization) of traditional medicine (75.0%) shows a percentage value agree greater than the health profession with strong scale.